Предмет: Математика, автор: Netel

решить уравнение: 6(b-3)=10-2(b+2)

Ответы

Автор ответа: Svet1ana
0

6(b-3)=10-2(b+2)

 

6b-18=10-2b-4

 

6b-18=6-2b

 

6b+2b=6+18

 

8b=24

 

b=24:8

 

b=3

__________________________________________________________

6cdot(3-3)=10-2cdot(3+2) (это проверка)

 

6cdot0=10-2cdot5

 

0=10-10

 

0=0

Автор ответа: tattiana2011
0

6(b-3)=10-2(b+2)

6b-18=10-2b-4

6b+2b=10-4+18

8b=24

b=24:8

b=3

проверка:

6(3-3)=10-2(3+2)

6*0=10-2*5

0=10-10

0=0 

Похожие вопросы